Analysis of Production Data Monitoring and Visualization Systems for Cyber-Physical Production Systems - Shalko, Y. (My University, 2022)
In this material, a study of modern systems of monitoring and visualization of production data for cyberphysical production systems (CPPS) based on Industry 4.0 was conducted. In the course of the study, the production monitoring system, its main components, and structure will be considered, in addition, we will pay attention to the advantages and disadvantages of similar systems.
Keywords: Industry 4.0; production monitoring system; Visualization Systems